2007
DOI: 10.1634/stemcells.2007-0128
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Marrow Cell Gene Expression, Protein Production, and Engraftment into Lung by Lung-Derived Microvesicles: A Novel Mechanism for Phenotype Modulation

Abstract: Numerous animal studies have demonstrated that adult marrow-derived cells can contribute to the cellular component of the lung. Lung injury is a major variable in this process; however, the mechanism remains unknown. We hypothesize that injured lung is capable of inducing epigenetic modifications of marrow cells, influencing them to assume phenotypic characteristics of lung cells. We report that under certain conditions, radiation-injured lung induced expression of pulmonary epithelial cell-specific genes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 57 publications
4
129
1
3
Order By: Relevance
“…We have recently described the delivery of lung-specifi c mRNA in microvesicles from radiation-injured lung to marrow cells with a functional change in the phenotype of the marrow cells [31]. In addition, Deregibus et al [32] have shown that microvesicles from endothelial progenitor cells could stimulate both in vitro and in vivo vasculogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently described the delivery of lung-specifi c mRNA in microvesicles from radiation-injured lung to marrow cells with a functional change in the phenotype of the marrow cells [31]. In addition, Deregibus et al [32] have shown that microvesicles from endothelial progenitor cells could stimulate both in vitro and in vivo vasculogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar vein, by studying murine lung originator cells and murine target marrow cells, Aliotta et al [28][29][30] showed that lung RNA was transferred to marrow cells inducing the expression of lung-specific mRNAs (surfactants A-D, Clara cell-specific protein, and aquaporin-5) and proteins and altering the function of marrow cells toward that of pulmonary cells. This later was shown by the increase in prosurfactantpositive pulmonary cells after transplant with vesicle exposed marrow.…”
Section: Vesicle Transfer Of Rna and Target Cell Phenotype Changementioning
confidence: 99%
“…In our own studies, we had demonstrated that the engraftment of GFP + marrow cells into lethally irradiated mice resulted in the appearance of GFP + pulmonary epithelial cells in the lungs of transplanted mice [28]. Subsequent studies showed that when lung tissue was cultured opposite murine marrow cells, but separated from them by a cell impermeable 0.4 mm membrane, the marrow cells expressed the pulmonary-specific mRNAs, surfactants A-D, aquaporin-5, and Clara cellspecific protein [29]. If the lungs were from mice exposed to 500 or 1,000 cGy whole body irradiation 5 days before cell harvest, the expression levels were significantly higher than if the lungs were from unirradiated mice.…”
Section: Providence Experiencementioning
confidence: 99%
“…5) (Valadi et al 2007). More recently, Aliotta et al (2007) demonstrated that RNAs contained in exosomes from radiation-treated lung cells could transfer a phenotype to bone marrow cells. In addition, conditioned media and secreted microvesicles derived from other cell types have been shown to alter the phenotypes of recipient cells.…”
Section: Potential For Horizontal Transfer Of Ptrosmentioning
confidence: 99%
“…The ribonome feeds information to the proteome via translation and thereby shapes its composition, but it also has a reciprocal regulatory relationship with it that sustains and limits RBP production within the ribonome (double arrow). Horizontal RNA transfer to the ribonome to Cell #2 (Valadi et al 2007) via exosome-mediated exchange directly affects both its ribonome and its proteome through RNA delivery and translation, but thereby affecting the phenotype of the recipient cell (BajKrzyworzeka et al 2006;Ratajczak et al 2006;Aliotta et al 2007. rhythms in particular is unclear, but it is logical to predict that such coordinating principles like PTROs may have a role in oscillatory processes involving transcription and translation. However, the potential expansion of information transfer among surrounding cells in tissues and organs whether it involves PTROs per se presents a novel possibility for connections between biological clocks that depend on cycles in gene expression to work properly in both the central nervous system and the peripheral organs.…”
Section: Cell #1mentioning
confidence: 99%